Adolescents’ mothers representations: intergenerational aspects in mother-infant relationship - Cabral, Stela (2012)
The woman experiences with her own mother and the representations about her can affect the exercise of  motherhood and the construction of maternal identity. This study examined the teenage mothers’ representations about their mothers and intergenerational aspects in the mother-baby relationship, according to a psychoanalytic perspective. Three primiparous adolescent mothers, which term babies were three to six months old, took part in the study. Interviews comprising sociodemographic data and Interview R, as well an observation in a breastfeeding situation. An interview with the adolescent’s mother was performed too. Results showed the influence of adolescents’ maternal model on the mother-baby relationship. Both constructive as well alienated identifications were found in the adolescents relationships with their own mothers. These results indicated the importance of investigating intergenerational aspects of adolescents’ representations in order to understand their maternal role accomplishment.